Moçambique Inquérito Demográfico e de Saúde 2011 - Ministerio da Saude - MISAU/Moçambique; Instituto Nacional de Estatística - INE/Moçambique; ICF International (MISA/Moçambique, INE/Moçambique and ICF International, 2013)
O Inquérito Demográfico e de Saúde (IDS) em Moçambique faze parte dum programa internacional de inquéritos (MEASURE DHS) desenvolvido pelo ICF International através de um contrato com a USAID, com o propósito de apoiar aos governos e instituições privadas dos países em desenvolvimento na realização de inquéritos nacionais por amostragem, nas áreas de população e saúde. O Programa MEASURE DHS tem por objectivo: • Subsidiar a formulação de políticas e implementação de programas nas áreas de população e saúde; • Aumentar a base internacional de dados sobre população e saúde para acompanhamento e avaliação; • Aprimorar metodologia de inquérito por amostragem, e • Consolidar, na área de inquérito, a capacidade técnica da instituição executora no país participante do Programa. O Programa DHS teve início em 1984 e, desde então, já foram realizados inquéritos em mais de 70 países da América Latina, Caribe, África, Ásia e Leste Europeu.
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; L - portuguese / português; M - survey / inquérito; Northern PEA; demographics / demografia; health / saúde

How active citizens can make a difference to improving service delivery in Mozambique: Phase 1: mapping citizen engagement programmes, initiatives and experiences - Programme, Citizen Engagement (2013)
The Citizen Engagement Program (CEP) supports citizens to monitor the quality of health and education service delivery in 4 of the 11 provinces of Mozambique, as well as to advocate for the improvement of the quality of those services at the district, provincial and national levels. The CEP aims at contributing towards the increased availability of relevant information for citizens to better access and benefit from services delivered by the public sector; improving citizens' capacity to assess service delivery and engage with service providers to improve the quality of health and education services at the primary and secondary levels; and supporting civil society organizations to leverage those findings within decision-making processes at higher levels. The programme will facilitate the dialogue between citizens / communities and service providers to improve the quality of services. The programme supports capacity-building, learning and experimentation, and will develop a robust system of monitoring and evaluation. The CEP will also analyse and build on experiences of service monitoring carried out by other actors and programmes, including other DFID and Irish Aid funded activities.
Accepted: 2017-12-05T13:07:47Z Publisher: (CEP) Citizen Engagement Programme / Cidadania e Participação
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; access to services / acesso a serviços; citizenship & participation / cidadania e participação; decentralization / descentralização; gender / género; health / saúde; ⛔ No DOI found